Ocular hypertension in patients with central/hemicentral retinal vein occlusions: cumulative prevalence and management - Călugăru, Dan (Int J Ophthalmol, 2018)
AIM: To prospectively evaluate the cumulative prevalence and the management of ocular hypertension (OH) in patients with unilateral acute central/hemicentral retinal vein occlusions (C/HCRVOs) over the course of 3y. METHODS: The study included 57 patients with unilateral acute C/HCRVOs. All patients underwent a comprehensive ophthalmological examination of both eyes. OH associated with C/HCRVO in patients showing a score >5% for the risk of conversion to primary open angle glaucoma (POAG) was treated with OH medication. The treatment aimed for a decrease in intraocular pressure (IOP) to <21 mm Hg with a >22% reduction from the initial values. The cumulative prevalence of OH and the effectiveness of treatment assessed by the cumulative prevalence of conversion from OH to POAG, were estimated. RESULTS: Fifteen patients had OH associated with C/HCRVOs, the cumulative prevalence of OH was 29.4% (95% confidence interval, 16.9-41.9). The mean value of the risk score of OH conversion to POAG for the 5 subsequent years was 11.7%±5.4%. The IOP significantly decreased from 25.67±2.16 mm Hg to 18.73±2.96 mm Hg. None of the OH patients converted to POAG during the follow-up period. CONCLUSION: The increased cumulative prevalence of OH in C/HCRVO patients indicates that OH is a risk factor for the appearance of venous occlusion. Patients with OH associated with C/HCRVO must be considered to be at high risk for conversion to POAG. Treatment with OH medications prevented conversion to POAG during the 3-year follow-up.